A Comparative Study of First and Third Year Prospective Elementary Teachers’ Attitude Towards Technology-Based Mathematics Assessment - Desri Rahmadhani; Zetra Hainul Putra; Eddy Noviana (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to determine how prospective elementary teachers' attitudes about technology-based mathematics assessment determine whether there are attitude differences between first and third-year prospective elementary teachers about technology-based mathematics assessment. This research is a comparative study with quantitative methods. The research data was conducted through an online survey, namely a questionnaire using Google Form. The populations of this study were 236 prospective elementary teachers with a sample size of 70 prospective elementary teachers. We use the proportion stratified random sampling technique to select the sample of this study. The results showed that the prospective elementary teachers have good attitudes toward technology-based mathematics assessment. This study also shows no difference between first and third-year prospective elementary teachers' attitudes towards the technology-based mathematics assessment.